Najrān en Arabie - la ville des 200 martyrs Chrétiens histoire et archéologie antiques et médiévales - Robin, Christian 1943- (Brill, 2025)
The Christians of Najrān are known by their martyrdom (November 523), described in Christian sources. According to Muslim tradition, the community was in relation with the polity of Medina, founded by Muḥammad in 622. Recent archeological discoveries attest this community in more details and bring substantial changes to our knowledge. Situated between Yemen and Medina, Najran was not only an influential Christian community persisting until the 10th century, but has seen remarkable transformations. The Christians of Najran underwent developments, some of which find an echo in the Qur'an, the earliest layer of Arabic script and the Muslim tradition
Erscheint voraussichtlich November 2024
Keywords: Christians / Saudi Arabia / Najrān (Province) / History; Martyrs / Saudi Arabia / Najrān (Province) / History; Excavations (Archaeology) / Saudi Arabia / Najrān (Province); Inscriptions / Saudi Arabia / Najrān (Province); Najrān (Saudi Arabia : Province) / History